2019
DOI: 10.1155/2019/6304851
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inducible Nitric Oxide Synthase (iNOS) in Human Cancer: A Systematic Review and Meta-Analysis

Abstract: Background. Inducible nitric oxide synthase (iNOS) is confirmed to regulate the production of nitric oxide (NO) when cells are exposed to external stimulus. Recent publications revealed that overexpression of iNOS predicted poor clinical outcomes for patients with malignant cancers, e.g., gastric, bladder, and colorectal cancers; however, several studies reported no obvious relationship between iNOS expression and prognosis of solid tumors. The aim of our study was to investigate the pooled effect of the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Therefore, each expression pattern may have distinct, or even opposing, relevance to the tumor biology and clinical behavior of tumors. A recent meta-analysis suggested that iNOS expression has an ominous prognostic impact in solid tumors, but the analysis was based on immunohistochemical data provided by published studies that used different cut-off points of iNOS expression and, furthermore, the analysis did not focus on the distinct patterns of expression within tumors [12]. For example, overexpression of iNOS by tumor-associated macrophages has been linked to a favorable prognosis in breast and lung cancer [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, each expression pattern may have distinct, or even opposing, relevance to the tumor biology and clinical behavior of tumors. A recent meta-analysis suggested that iNOS expression has an ominous prognostic impact in solid tumors, but the analysis was based on immunohistochemical data provided by published studies that used different cut-off points of iNOS expression and, furthermore, the analysis did not focus on the distinct patterns of expression within tumors [12]. For example, overexpression of iNOS by tumor-associated macrophages has been linked to a favorable prognosis in breast and lung cancer [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NOS has been reported in many cancers, including breast, cervical, head and neck, and lung cancer (29), and the presence of NO in the cancer area has been linked to the aggressiveness of the diseases (12). The expression of inducible nitric oxide synthase (iNOS) in cancer cells as well as the expression of NOS in the environment of cancers have been shown to predict poor survival (30). Molecular explanations on how NO regulates chemotherapeutic resistance as well as attenuates cancer cell response to immune cell-mediated death have been suggested by many researchers (11,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the intrinsic feature of malignant cells required to produce NO, mostly by constitutive expression of iNOS, is related to poor prognosis. Liao et al recently reported a highly significant association between iNOS expression and disease outcome following overall, cause-specific, and disease-free survival [119]. According to results obtained through meta-analysis, all parameters were remarkably worse in patients with solid tumors expressing iNOS.…”
Section: No In Initial and Acquired Resistance To Therapymentioning
confidence: 99%